Association between progesterone concentration and endometrial gene expression in dairy cows - Madoz, Laura Vanina (2020)
The objective of this study was to evaluate the association between progesterone concentration on Days 4 and 9 of the estrus cycle and endometrial transcriptome at Day 9 in lactating grazing dairy cows. Blood samples were obtained on Days 0, 4, and 9 for progesterone measurement by chemiluminescence. Cows were assigned to one of the following groups (n = 3 per group): cows with low physiological progesterone on Day 4, cows in anestrous, cows with high physiological progesterone on Day 4, and superovulated cows. Endometrial biopsy samples were obtained on Day 9 for RNA sequencing. Quality control and determination of differentially expressed genes (false discovery rate <0.05) were determined using the edgeR package for R software. We identified 3,042 differentially expressed genes among the 4 groups. Cows having high physiological progesterone and superovulated cows showed high similarities and clustered apart from those in anestrus or having low physiological progesterone. Functional analysis using Database for Annotation, Visualization, and Integrated Discovery revealed that endometrial genes upregulated by low progesterone concentration are enriched genes involved in the immune system and inflammatory response. Conversely, cows with high physiological progesterone concentration presented an endometrial transcriptome with similarities to cows with good genetic merit for fertility, showing upregulation of genes related to uterine relaxation–contraction, focal adhesion, GnRH signaling pathway, and epidermal growth factor–like related terms, suggesting a favorable embryo environment. In conclusion, our results support the concept that there is a threshold of progesterone concentration at the beginning of the luteal phase associated with endometrial expression of critical genes involved in the preparation of the uterine environment for embryo implantation.